Pin signature verification using wavelet transform - Tee, Elok Robert; Selvanathan, N. (Faculty of Computer Science and Information Technology, University of Malaya, 1996)
The personal identification number signature (PIN signature) is a method of remembering and typing the PIN using the de facto standard numeric keypad format. The PIN signature affords a second level security in that it enhances the PIN with additional information on the user, i.e. the profile of its input. The PIN signature reference profile can be viewed as a signal vector and can thus be enhanced and verified as to its physiological characteristics using wavelet transform. The result of this analysis is presented.